The effect of MRI-based screening and selection on the prevalence of syringomyelia in the Dutch and Danish Cavalier King Charles Spaniels - Limpens, Citlalli; Smits, Vivian T. M.; Fieten, Hille; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2024)
Introduction Syringomyelia (SM) is a heritable disorder causing a fluid filled cavity (FFC) in the spinal cord with a reported overall prevalence of 39 to 46% in the Cavalier King Charles Spaniels (CKCS). Breeders started screening their CKCS with MRI in the Netherlands since 2004 and in Denmark since 2015. The goal of this study was to evaluate the effect of MRI-based selection in breeding on the prevalence of SM. Method MRI scans of 2,125 purebred CKCS were available. SM was defined as having a visible FFC in the spinal cord. The prevalence of SM per year of birth was calculated, and a logistic regression was used to evaluate the affected status of offspring from affected versus unaffected parents and age category of the parent and study the combined effect of parental status and age-category to evaluate the effect on the affected status of the offspring. Results The mean FFC in affected CKCS was 2.03 ± 1.47 mm and ranged from 0.5 to 9 mm (median of 1.5 mm). An age effect exists as older CKCS, which has a higher frequency of being affected compared with younger CKCS. There was no significant sex predilection for SM in this dataset. The mean prevalence of SM decreased slightly from 38% (2010–2014; 2.8 ± 1.3 years of age (mean ± sd); median 2.6 years) to 27% (2015–2019; 2.4 ± 1.2 years of age; median 2.1 years) in the screened population of CKCS (p = 4.3e-07). Breeding with two affected parents increased the odds ratio with 3.08 for producing affected offspring (95% CI 1.58–6.04) compared with breeding with unaffected parents. Discussion MRI-based screening and selection against SM led to a minimal decrease in the prevalence of SM in the Dutch and Danish CKCS population. Breeding with dogs with SM significantly increases the risk of affected offspring. As the disorder is progressive with age, and based on the results of this study, MRI-based screening for all CKCS is recommended at an age of 3 years or older, and to reduce SM more effectively, CKCS affected with SM should not be used for breeding.